Comparative Raman scattering study of Ba₃MSb₂O₉ (M=Zn, Co and Cu) - Glamazda, A.; Lemmens, P.; Do, S.-H.; Choi, K.-Y. (Физика низких температур, 2017)
Raman spectroscopy is combined with lattice dynamic calculations to investigate the magnetic and structural properties of the 6H-perovskite compounds Ba₃MSb₂O₉ (M = Zn, Co and Cu). Unlike the nonmagnetic Ba₃ZnSb₂O₉ compound, the magnetic counterparts Ba₃MSb₂O₉ (M = Co and Cu) show both lattice anomalies for temperatures below 100 K and develop highly correlated spin states below 50 K. This is ascribed to an instability of conventional magnetic excitations for the equilateral triangular antiferromagnet Ba₃CoSb₂O₉ and a coexistence of spin-orbital liquid and random singlet state for the decorated honeycomb compound Ba₃CuSb₂O₉ containing a nearly identical volume fraction of hexagonal and orthorhombic phases. Our results demonstrate that Ba₃MSb₂O₉ provides a rich reservoir for hosting diverse magnetic and structural phases as a function of the metal ion M.